An Analytical Approach to Probabilistic Dynamic Security Assessment of Power Systems Incorporating Wind Farms. (December 2017) - Liu, Yanli; Yue, Ziyuan; Yu, Yixin
Abstract: An analytical approach to probabilistic dynamic security assessment of power systems incorporating wind farms is proposed. As the most important and complex step of the evaluation process, the probability of transient stability given a specific fault and uncertainties of output power of wind farm and load is calculated analytically based on the practical dynamic security region of power system with double fed induction generator and Cornish-Fisher expansion. The proposed method can provide meaningful and reliable evaluation results with high accuracy and much less computing time compared with Monte Carlo simulation.